The Role of the Kappa Opioid System in Comorbid Pain and Psychiatric Disorders: Function and Implications - Ji, Miao-Jin; Yang, Jiao; Gao, Zhi-Qiang; Zhang, Liang; Liu, Chao (Frontiers in Neuroscience, 2021)
Both pain and psychiatric disorders such as anxiety and depression significantly impact quality of life for the sufferer. The two also share a strong pathological link: chronic pain-induced negative affect drives vulnerability to psychiatric disorders, whilst patients with comorbid psychiatric disorders tend to experience exacerbated pain. However, the mechanisms responsible for the comorbidity of pain and psychiatric disorders remain unclear. It is well established that the kappa opioid system contributes to depressive and dysphoric states. Emerging studies of chronic pain have revealed the role and mechanisms of the kappa opioid system in pain processing and, in particular, in the associated pathological alteration of affection. Here, we discuss the key findings and summarize compounds acting on the kappa opioid system that are potential candidates for therapeutic strategies against comorbid pain and psychiatric disorders.